COMMUNICATION BETWEEN SPOUSES FOR GENDER EQUALITY IN CONTRACEPTION USE - Puri Kusuma Dwi Putri (Universitas Muhammadiyah Jakarta, 2019)
The use of contraceptives is still a gender bias for family based health development. Why is always woman who have been the subject of family planning? The use of contraceptives is not as the nature of women. The family has not yet become a place where gender equality begins. It might due to the values, norms, and culture inherited from parents, that women can willingly accept every word of the husband. The role of women in the success of male family planning is also spearheading the development of national development originated from a family as the women get a lot of information about family planning. Mindset of the women also need to be changed with the women as the subject of family planning, there is also a fear of her husband having an affair as they refuse the vasectomy. In another side, there is also opinion that men is also important in family planning as the side effects of the use of contraceptives are more widely experienced by women.Redefining the meaning of the family can mean the participation of men in the use of contraceptives, such as those conducted by Ismail Hussein, PriyoUtomo, Suku Using, and the general public who participated in the World Vasectomy Day. Speaking of family planning and Knowledge of reproductive health in the family is not as taboo and sensitive talks. Thus, family communication is a forum for gender equality in the use contraceptives which aims to improve the welfare of family. Keywords: contraceptives, women, family, gender equality, participation